Behavioral and psychosocial factors of quality of life among adult people living with HIV on Highly Active Antiretroviral Therapy, in public hospitals of Southwest Ethiopia - Abreha Addis Gesese; Yitages Getachew Desta; Endale Zenebe Behire (Public Library of Science (PLoS), 2022)
Despite the availability of Highly Active Antiretroviral Therapy, the quality of life (QOL) of People Living with HIV/AIDS (PLWHIV) has continued to be affected. However, previous studies focused on the magnitude and clinical determinants which lacks behavioral and psychosocial factors of QOL. Thus, this study aimed to identify behavioral and psychosocial determinants of QOL among Adult PLWHIV on HARRT, in Public Hospitals of Jimma Zone, South West, Ethiopia, 2018. A cross-sectional study design was conducted in Public Hospitals of Jimma Zone, Southwest Ethiopia from March 10 to April 10/2018. QOL of was measured using WHOQOL-HIV BREF instrument. A simple random sampling technique was employed to enroll study participants. A pretested interviewer-administered structured questionnaire was used to collect data. Then, data were entered into Epi-Data version 3.1 and analyzed using SPSS version 20. Bivariate and multiple variable logistic regression analyses were also performed. A total of 300 respondents were enrolled into the study yielding a response rate of 97.7%. The majority of respondents were from urban residence and between 35-44 years of age. About 47% of respondents have ever used substances, and 58.3% have obtained social support. Nearly 80% and 26.3% of the study participants were stigmatized and severely depressed. More than half of the study participants had good overall QoL with the highest domain QOL in level of independence and lowest in social relations. Factors associated with poor physical health include being government employee AOR 0.33 95%CI (0.15, 0.69), from private business AOR 0.33 95%CI (0.14, 0.79), being 1st wealth quintile AOR 2.44 95%CI (1.16, 5.14), and not obtaining financial support AOR 4.27 95%CI (1.94, 9.42). Lower wealth index has been associated with almost all domain scores of poor QOL except spiritual domain. More than half of the respondents had good overall QoL with the highest domain score in level of independence and lowest in social relations domain. Several factors have contributed to poor domain QOL of PLWHIV. Therefore, it will become all the most important to develop effective strategies, policies and programs targeting people living with HIV. Emphasis should be given to the socio-economic factors that affect their QOL on HAART. Professional counseling and guidance with life skill packages should be strengthened to cope up with adverse behavioral factors. Finally, psychosocial support should be provided from all responsible bodies.